YouTube as a source of information in cardiopulmonary resuscitation for 2020 AHA Resuscitation Guidelines - Yazla,Merve; Şafak,Tuba; Aksu,Şakir Hakan; Savran,Kadiriye; Aydogan,Rafet Fatih; Arslan,Mustafa; Koçak,Abdullah Osman; Katipoğlu,Burak (PeerJ, 2024)
Background The Internet has transformed global information access, particularly through platforms like YouTube, which launched in 1995 and has since become the second largest search engine worldwide with over two billion monthly users. While YouTube offers extensive educational content, including health topics like cardiopulmonary resuscitation (CPR) and basic life support (BLS), it also poses risks due to potential misinformation. Our study focuses on evaluating the accuracy of CPR and BLS videos on YouTube according to the latest 2020 American Heart Association (AHA) guidelines. This research aims to highlight inconsistencies and provide insights into improving YouTube as a reliable educational resource for both lay rescuers and healthcare professionals. Methods In this cross-sectional observational study, English YouTube videos uploaded between October 21, 2020, and May 1, 2023, were searched using keywords related to CPR and basic life support. Videos were assessed for their source, duration, views, use of human or mannequin models, and mean assessment scores by two emergency medicine physicians. A third physician’s opinion was sought in cases of disagreement. The first assessment evaluated video validity based on specified information criteria, while the second assessed their ability to convey advanced medical information aligned with the 2020 AHA guidelines. Results In this study, 201 English YouTube videos uploaded between October 21, 2020, and May 1, 2023, were evaluated based on search terms related to CPR and BLS, resulting in 95 videos meeting inclusion criteria after excluding 106 due to various reasons. Most included videos were from healthcare professionals (49.5%), followed by anonymous sources (29.5%) and official medical organizations (21.1%). Video durations ranged widely from 43 to 6,019 seconds, with an average of 692 seconds. Videos featuring mannequins predominated (91.6%), followed by those using human subjects (5.3%) or both (3.2%). Healthcare professional and official medical organization videos scoring significantly higher than those of unknown origin (p = 0.001). Video length did not correlate significantly with view counts, although shorter videos under 5 minutes tended to have higher average views. Discussion The results presented in this study demonstrated that English-language videos on YouTube related to BLS and CPR, throughout the study period, did not conform to the 2020 AHA guidelines in terms of providing basic information for lay rescuers. Furthermore, healthcare professionals cannot obtain advanced medical knowledge through these videos. We recommend a professional oversight mechanism in health-related videos that does not tolerate such misinformation.
Keywords: Cardiopulmonary resuscitation; Basic life support; YouTube education